Collaborative virtual reality application for interior design - Haziq Izwan Rahmat; Suzana Ahmad; Marina Ismail (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Virtual Reality (VR) is currently popular technology that has been used by people in various areas such as architecture, medical, training and many more.  In this paper, the researcher proposed collaborative VR for interior design that allows customer and designer work together at different location.  Commonly, the designer draw their design in two-dimensional (2D) graphics at the drawing paper and presents to the customer.  However, 2D drawings led to an ambiguity, indistrinct and uncertainty on the design.  In addition, redesign any changes lead to re-build the prototype.  These will be costly and wasting time, therefore, researcher proposed collaborative VR application which provide an intense feelings about the design which is presented in form of three-dimensional (3D) graphics.  Additionally, proposed application would allow the designer and customer to work in real-time.  In conclusion, collaborative VR will give the benefits for interior design manufacturing to prosper along with current technology.